Accounting in Ontological, Epistemological and Axiological Reviews - Hajrah Hamzah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Accounting science is part of the philosophy of science. This paper aims to see and show how capable the philosophy of science underlies various sciences, especially in the field of accounting. Basically The science of accounting develops within the framework of the philosophy of science which is the basis and direction, namely through ontology, epistemology and axiology as well as paradigms and is limited by the methodological scientific method and the development of the times influencing the development of accounting science. By examining these aspects, it is hoped that it will be known to what extent the contribution of the philosophy of science as a foundation in the development of accounting theories, methods, approaches, principles and standards takes place from time to time